1997
DOI: 10.1038/41771
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness, hypoalgesia and high blood pressure in mice lacking the adenosine A2a receptor

Abstract: Adenosine is released from metabolically active cells by facilitated diffusion, and is generated extracellularly by degradation of released ATP. It is a potent biological mediator that modulates the activity of numerous cell types, including various neuronal populations, platelets, neutrophils and mast cells, and smooth muscle cells in bronchi and vasculature. Most of these effects help to protect cells and tissues during stress conditions such as ischaemia. Adenosine mediates its effects through four receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
595
6
10

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 840 publications
(649 citation statements)
references
References 24 publications
38
595
6
10
Order By: Relevance
“…Thus, BC1-deficient mice showed reduced exploratory behaviour in the barrier test, the open-field test and the complex-alley maze test, and were reluctant to enter open arms in the elevated plus-maze. Reduced exploratory behaviour may also be mediated by mechanisms regulating anxiety [6,23]. Importantly, observations in the laboratory on exploration and anxiety-related behaviour were confirmed by results from the semi-naturalistic outdoor studies.…”
Section: Bc1 Rna Modulates Expression Of Exploratory Behaviour But Nomentioning
confidence: 67%
“…Thus, BC1-deficient mice showed reduced exploratory behaviour in the barrier test, the open-field test and the complex-alley maze test, and were reluctant to enter open arms in the elevated plus-maze. Reduced exploratory behaviour may also be mediated by mechanisms regulating anxiety [6,23]. Importantly, observations in the laboratory on exploration and anxiety-related behaviour were confirmed by results from the semi-naturalistic outdoor studies.…”
Section: Bc1 Rna Modulates Expression Of Exploratory Behaviour But Nomentioning
confidence: 67%
“…In spite of these di erences, our data con®rm an important role for A 2a receptors in vascular tone regulation, and suggest that the systemic response mediated by these receptors is prevalently linked to the release of NO, probably from endothelial cells. The role of endothelial receptors in the response to adenosine was previously suggested by the evidence from Nees (1989) blood pressure was, in fact, observed in A 2a receptor gene knockout-mice (Ledent et al, 1997).…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, mice lacking A2AR (Chen et al, 1999;Ledent et al, 1997) have been shown to demonstrate reduced sensitivity to the hypnotic effects of alcohol, increased alcohol consumption, and reduced alcohol-withdrawal seizures (El Yacoubi et al, 2001;Naassila et al, 2002). As a result, antagonism of A2AR signaling could be useful in the treatment of alcohol withdrawal symptoms; however, since inhibition of A2AR also results in increased alcohol consumption, the mechanisms through which the A2AR mediates each of these effects should be further delineated to identify a more specific therapeutic approach.…”
Section: Adenosine Receptor Signaling In Ethanol Drinkingmentioning
confidence: 99%